Social welfare and economic equality: healthcare expenditure as a moderator - Liu, Gai (Frontiers in Public Health, 2025)
IntroductionThis study aims to examine the impact of social welfare expenditure on household economic equality, as well as the moderating effect of healthcare expenditure on this relationship. Additionally, the study seeks to propose policy recommendations to address universal health issues and enhance the overall level of national welfare.MethodsUtilizing the CFPS database, this study employs a two-way fixed effects model, along with moderating effect models, to investigate the impacts of social welfare expenditure, household healthcare expenditures, family education expenditures, and household housing expenditures on the advancement of household economic equality.ResultsThis study found that for every 1% increase in social welfare expenditure, family economic equality can be improved by 0.033. However, the study also revealed a decrease of 0.069 in the employment quality of the head of the household, indicating that social welfare expenditure negatively impacts this employment quality. Additionally, the moderating effect analysis demonstrated a significantly negative interaction between healthcare expenditure and social welfare expenditure, suggesting that family healthcare expenditure diminishes the positive effect of social welfare expenditure on the advancement of family economic equality.ConclusionThe government should optimize and expand the level and efficiency of social welfare expenditure. For instance, the government could implement a ‘universal free medical care’ policy. Specific measures may include waiving medical insurance premiums, ensuring full reimbursement, and adopting a ‘treatment first, settlement later’ system. These initiatives will effectively alleviate the economic burden of health-related issues on families and promote equitable development of family economies. Furthermore, the government should also enhance policies related to employment quality. Such measures will contribute to optimizing the level and efficiency of social welfare expenditure, fostering economic equality, and narrowing the gap between the rich and the poor.